Penerapan Disprogramming Pada Revitalisasi Pasar Bulu Semarang - Utari Sulistyandari; Angger Sukma Mahendra; Radya Wafi Adyatma; Putri Ayu Fatimatuzzahro; Vania Erli; Rabbani Kharismawan; Bambang Soemardiono (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Pasar Bulu Semarang has experienced a decline in activity despite being revitalized, due to spatial integration issues, especially in terms of circulation, visibility, and connectivity to public transportation. Traditional market revitalization studies have rarely explored spatial strategies that integrate spatial programs. This study uses a force-based framework and design-by-research approach to examine disprogramming as a spatial design method that integrates markets with terminals. Through site observation, precedent studies, and literature reviews, ten main design criteria related to circulation, observability, and spatial flexibility were generated, which were analyzed in a spatial relationship matrix to identify potential program harmonization and contradictions. The results show that disprogramming is effective in creating adaptive and contextual hybrid public spaces. This study contributes a structured design framework for market revitalization strategies in dense urban areas.